2006
DOI: 10.1007/s10600-006-0179-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 20S-protopanaxadiol 20-O-β-D-glucopyranoside, a metabolite of Panax ginseng glycosides, and compounds related to it

Abstract: Extract of Panax ginseng C. A. Meyer root, which is constantly attracting attention to itself owing to the breadth and variety of its biological activity, contains triterpene glycosides, which have been the subject of numerous investigations. Ginseng glycosides are transformed by intestinal microflora in the gastro-intestinal tract into compounds with new biological properties. In the last few years, the properties and mechanism of action of one of the main metabolites of ginseng glycosides, 20S-protopanaxadio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…The HRMS data of 3 showed a similar [M + HCOOH − H] − m/z with CK and Rh2 of 667.4787, calculated for a molecular formula of C 36 H 62 O 8 (Figure 11). According to literature [42,43,44], the major structural difference between Rh2 and CK is the linking position of the glucosyl moiety, leading to obvious variations of chemical shifts at C-3, C-20 and glucosyl C-1″. As shown in Table 4 and Figure 12, metabolite 3 was proven to be CK due to the identical chemical shifts which distinguished it from Rh2 at C-3 (δ = 78.16), C-20 (δ = 83.55) and C-1″ (δ = 96.92).…”
Section: Resultsmentioning
confidence: 99%
“…The HRMS data of 3 showed a similar [M + HCOOH − H] − m/z with CK and Rh2 of 667.4787, calculated for a molecular formula of C 36 H 62 O 8 (Figure 11). According to literature [42,43,44], the major structural difference between Rh2 and CK is the linking position of the glucosyl moiety, leading to obvious variations of chemical shifts at C-3, C-20 and glucosyl C-1″. As shown in Table 4 and Figure 12, metabolite 3 was proven to be CK due to the identical chemical shifts which distinguished it from Rh2 at C-3 (δ = 78.16), C-20 (δ = 83.55) and C-1″ (δ = 96.92).…”
Section: Resultsmentioning
confidence: 99%
“…sodium borohydride, or metallic sodium in toluene/2‐propanol or Birch conditions) did not afford protopanaxadiol 2 but regenerate 3β,12α‐diol 28 as the sole product. It is worth mentioning that diketone 29 has already been described by Atopkina and Denisenko for the semi‐synthetic preparation of ginsenoside glycosides and, in addition, our strategy allows the formal total synthesis, of chikusetsusaponin‐LT 8 30 , a bioactive ginsenoside isolated from Panax japonicus …”
Section: Resultsmentioning
confidence: 94%
“…Deprotection of the hydroxyl groups afforded 12‐ epi ‐protopaxadiol 28 after 19 steps with an overall 1.0 % yield. Diol 28 was further oxidized into diketone 29 , but attempts to reduce this ketone (e.g. sodium borohydride, or metallic sodium in toluene/2‐propanol or Birch conditions) did not afford protopanaxadiol 2 but regenerate 3β,12α‐diol 28 as the sole product.…”
Section: Resultsmentioning
confidence: 99%
“…Hasegawa proposed that the metabolized M1 was esterified with fatty acids in the liver, which resulted in longer permanence in the body and exhibits the antitumor activities, and concluded that ginsenoside is a pro-drug activated in the body by deglycosylation and esterification [ 2 , 11 ]. Compared to the fact that much attention has been devoted to the bioactivities, especially anticancer activity of M1 [ 15 , 16 , 17 ], there is scant synthetic work related to M1 in the literature [ 26 , 27 ]. Recently, we synthesized the monoesters of M1 via introduction of acyl groups onto the 6'-OH of the glucose moiety in M1 and found the esterified products exhibited cytotoxicity against several human cancer cell lines (breast cancer MCF-7, skin melanoma SK-MEL-2 and human ovarian carcinoma B16) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%